Analisa Data API Pasien Covid-19 di Dunia menggunakan Power BI - Achmad Syirod; Agung Triayudi; Ira Diana Sholihati (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
Passing a year since the start of the Covid-19 pandemic, it has taken many lives and changed the way humans interact and navigate the world. Although the use of vaccines is implemented, the number of victims continues to grow in the world. Information about Covid-19 data is spread in every country, so there is a need for a place to view the data quickly, accurately, and flexibly between applications. By using the API method or Application Programming Interface, the data can be obtained via the internet. At this stage, the research is carried out through system planning, data collection, and data analysis. From the results of the research, it is known that Power BI is able to pull and process the Covid-19 API data into various kinds of graphs. Then from the results of these graphs, it can be concluded that for the total cases, the total recoveries and the total deaths were held by the USA (United States). For the highest total new cases by the state of India. Then for the highest percentage of the total cases by continent held by the Asian continent.